The Global Advance of Genome-Edited Plants to the Market: The Key Role of Chile in Its Development - Miguel A. Sánchez (Plants)
The global advancement of genome-edited plants toward commercialization has been significantly shaped by the functionality and flexibility of some regulatory frameworks governing plant genome editing. These frameworks vary widely across countries, reflecting diverse approaches to assessing and managing the risks and benefits of genome-editing technologies. While some nations have adopted product-based frameworks that focus on the characteristics of the final plant rather than the technique used, others rely on more restrictive process-based regulations. This variability influences the pace of innovation, the types of products able to enter the market, and their global trade potential. Chile stands out as a leader in this landscape, having implemented a science-driven and flexible regulatory framework. Its system promotes innovation by facilitating genome-edited plant research and development, field testing, and local commercialization. This regulatory adaptability positions Chile as a critical player in supporting the global integration of genome-editing technologies into agriculture, fostering advancements that address food security, sustainability, and climate resilience.